Cold, hard steel - Arnold-Forster, Agnes (Manchester University Press, 2023)
Brilliant, volatile, and invariably male, the surgeon stereotype is a widespread and instantly recognisable part of Western culture. Setting out to anatomise this stereotype, Cold, Hard Steel offers an exciting new history of modern and contemporary British surgery. The book draws on archival materials and original interviews with surgeons, analysing them alongside a range of fictional depictions, from the Doctor in the House novels to Mills & Boon romances and the pioneering soap opera Emergency Ward 10. Presenting a unique social, cultural, and emotional history, it sheds light on the development and maintenance of the surgical stereotype and explains why it has proved so enduring. At the same time, the book explores the more candid and compassionate image of the surgeon that has begun to emerge in recent years, revealing how a series of high-profile memoirs both challenge the surgical stereotype and simultaneously confirm it.